2023
DOI: 10.1186/s12894-023-01199-5
|View full text |Cite
|
Sign up to set email alerts
|

High-pressure balloon dilatation of primary obstructive megaureter in children: a systematic review

Abstract: Objective We aimed to evaluate the effectiveness and complication rates of endoscopic high-pressure balloon dilatation (HPBD) in treating primary obstructive megaureter (POM) in children based on current literature. Specifically, we wanted to clarify the evidence on the use of HPBD in children under one year of age. Methods A systematic search of the literature was performed via several databases. The preferred reporting items for systematic review… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 43 publications
0
2
0
Order By: Relevance
“…19 However, despite the perceived benefits of a fully endoscopic intervention, there are some drawbacks. These include the overall success rate (which can be as low as 71%, based on a recent systematic review 20 ), the risk of secondary VUR, inability to gain ureteral access in all cases, difficult stent deployment in a tortuous ureter, stent displacement, and risk of recurrent ureteral stenosis. 21 In addition, the procedure requires the use of fluoroscopy and, depending on the caliber and length of the stenotic segment, specialized equipment for access and dilation.…”
Section: Discussionmentioning
confidence: 99%
“…19 However, despite the perceived benefits of a fully endoscopic intervention, there are some drawbacks. These include the overall success rate (which can be as low as 71%, based on a recent systematic review 20 ), the risk of secondary VUR, inability to gain ureteral access in all cases, difficult stent deployment in a tortuous ureter, stent displacement, and risk of recurrent ureteral stenosis. 21 In addition, the procedure requires the use of fluoroscopy and, depending on the caliber and length of the stenotic segment, specialized equipment for access and dilation.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, Ripatti et al suggested that HPBD seems safe and could serve as the primary treatment for symptomatic PMU, yet additional comparative studies are required to evaluate its efficacy in infants and its long-term effects, with the challenge remaining in accurately identifying patients who would benefit from HPBD due to the complex nature of PMU [ 49 ].…”
Section: Surgical Approachesmentioning
confidence: 99%